Iodine intake monitoring in neonatal population in the Czech Republic: alarming numbers in 2020 - Světnička, Martin; Hedelová, Monika; Vinohradská, Hana; El-Lababidi, Eva (Casopis lekaru ceskych, 2021)
Thanks to comprehensive and long-term preventive programs, the Czech Republic has taken its place among the countries with a resolved iodine deficiency at all population levels since 2004. A sensitive indicator of iodine supply to the population, which can also be used to monitor the efficiency of prophylactic programs, is the TSH assessment in the nationwide neonatal screening of congenital hypothyroidism. Nevertheless, recent results of neonatal TSH show that newborns and pregnant women remain very risky groups and their iodine saturation is borderline. In recent years, the percentage of newborns with TSH 5-15 mIU/l has already risen above the 3% mark, i.e. mild iodine deficiency in major part of the Czech Republic (3.8 % in Bohemia, 2.8% in Moravia in 2019 and 4.7 % in Bohemia, 2.9% in Moravia in 2020). For some smaller areas, the values are even higher, which can be related, for example, to the social patterns of the population. The result may be not only the exclusion of the Czech Republic from the list of countries with resolved iodine deficiency, but especially adverse consequences for the cognitive development of the future generation. Therefore, it is essential to intensify nation-wide intervention among both the professional and general public. In this regard, adherence to the supplementation of pregnant and breastfeeding women is crucial with 150-200 μg of iodide in addition to nutritional iodine intake.
Keywords: Female; novorozenec; ženské pohlaví; Iodine; neonatal TSH; Nutritional Status; lidé; Infant, Newborn; těhotenství; iodine supply in pregnancy; nutriční stav; disorders of mental development; Czech Republic; neonatal screening; Česká republika; jod; iodine deficiency; Pregnancy; preventive measures; Humans